Determinan Loyalitas Pengguna Smartphone Samsung: Pengalaman Merek, Inovasi Produk, dan Kualitas Produk - Malika Alya Amelia; Ibnu Cahyo Ramadhan (Soratekno Publisher, 2025)
This study aims to analyze the influence of brand experience, product innovation, and product quality on the loyalty of Samsung smartphone users. The research focuses on consumers who actively use Samsung smartphones, with the main variables examined including brand experience, product innovation, and product quality. The research method employed is non-probability sampling using a purposive sampling technique, in which samples are selected based on specific criteria relevant to the research objectives. Since the total population of users cannot be precisely determined, the sample size was calculated using the Rao Purba formula. The results indicate that brand experience, product innovation, and product quality simultaneously have a significant effect on the loyalty of Samsung smartphone users. Brand experience has a significant partial effect on user loyalty. Product innovation also partially influences user loyalty. Product quality has a significant effect on user loyalty. Factors such as durability and strong performance enhance customer satisfaction and strengthen loyalty toward the Samsung brand. These findings confirm that brand experience, product innovation, and product quality are the key factors in building user loyalty.